2022
DOI: 10.3389/fpsyg.2022.936286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adolescents’ tendency to catastrophise on non-suicidal self-injury behaviour: A moderated mediation model

Abstract: Adolescence is the peak period of non-suicidal self-injury (NSSI) behaviour, and it is also a period when the prevention and intervention in NSSI are frequently required. To explore the relationship between catastrophising and NSSI and its mechanism, the mediating effects of parental support and negative emotions on catastrophising and NSSI were analysed. A questionnaire was administered to 401 middle school students with a history of NSSI behaviour from 12 schools in Guangxi. (1) Adolescents’ catastrophising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…All the papers (100%) used the terms emotion dysregulation or emotion regulation at least one time in the manuscripts. Four times the term was searched in view of relation NSSI and suicide (Brausch et al, 2022;Brausch & Woods, 2019;Chen & Chun, 2019;Kim et al, 2020), and ten times was combined with other dimensions (Cerutti et al, 2018;Gu et al, 2022;Kiekens et al, 2015;Lan et al, 2022;Liu et al, 2022;Lutz et al, 2022;Mozafari et al, 2022;Wan et al, 2020;Xavier et al, 2018;Zhou et al, 2022). These results reinforce the strong association between NSSI and suicide risk in adolescents, as an established important factor pointed out in the specialized literature (Brausch et al, 2022;Brausch & Woods, 2019;Chen & Chun, 2019;Kim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the papers (100%) used the terms emotion dysregulation or emotion regulation at least one time in the manuscripts. Four times the term was searched in view of relation NSSI and suicide (Brausch et al, 2022;Brausch & Woods, 2019;Chen & Chun, 2019;Kim et al, 2020), and ten times was combined with other dimensions (Cerutti et al, 2018;Gu et al, 2022;Kiekens et al, 2015;Lan et al, 2022;Liu et al, 2022;Lutz et al, 2022;Mozafari et al, 2022;Wan et al, 2020;Xavier et al, 2018;Zhou et al, 2022). These results reinforce the strong association between NSSI and suicide risk in adolescents, as an established important factor pointed out in the specialized literature (Brausch et al, 2022;Brausch & Woods, 2019;Chen & Chun, 2019;Kim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This kind of perfectionism describes the propensity "to interpret even the smallest of mistakes as indicative of failure, combined with a belief that failure will result in the loss of others' respect" (Kawamura & Frost, 2004, as cited in Gu et al, 2022. Lan et al (2022) explore the relationship between catastrophizing emotion, NSSI, and parental support for negative emotions, and found that catastrophizing tendency may contribute to the development of negative emotions, and it leads to triggering NSSI behavior on several levels. Catastrophizing emotion is a potential cognitive distortion of thinking, which involves a tendency to amplify negative feelings, anguish, and its possible bad consequences.…”
Section: Emotion Regulation 12 48mentioning
confidence: 99%
“…Prior research has investigated the correlation between NSSI and variables, including "catastrophic" (a non-adaptive regulatory strategy) factors [ 26 , 27 ]. As per the cognitive-emotion paradigm, individuals who experience strong negative emotions, find it difficult to regulate these feelings, and perceive NSSI as a beneficial method for handling these emotions are more likely to engage in NSSI [ 28 ].…”
Section: Research Backgroundmentioning
confidence: 99%
“…The reported prevalence of NSSI among Chinese adolescents ranges from 14-34%. (Han et al, 2018;Li et al, 2020;Lan et al, 2022;Hu et al, 2023), indicating the severity of the issue. Adolescent bullying has also been discussed extensively.…”
Section: Introductionmentioning
confidence: 99%